The neuronal nitric oxide synthase gene is critically involved in neurobehavioral effects of alcohol - Spanagel, Rainer; Siegmund, Sören Volker; Cowen, Michael; Schroff, Karl-Christian; Schumann, Gunter; Fiserova, Magdalena; Sillaber, Inge; Wellek, Stefan; Singer, Manfred V.; Putzke, Jörg (The journal of neuroscience, 2002)
In the present study, we describe a new role of the neuronal nitric oxide synthase (nNOS) gene in the regulation of alcohol drinking behavior. Mice deficient in the nNOS gene (nNOS −/−) and wild-type control mice were submitted to a two-bottle free-choice procedure with either water or increasing concentrations of alcohol (2-16%) for 6 weeks. nNOS −/− mice did not differ in consumption and preference for low alcohol concentrations from wild-type animals; however, nNOS −/− mice consumed sixfold more alcohol from highly concentrated alcohol solutions than wild-type mice. Taste studies with either sucrose or quinine solutions revealed that alcohol intake in nNOS −/− and wild-type mice is associated, at least in part, with sweet solution intake but not with the taste of bitterness. When compared with wild-type mice, the nNOS −/− mice were found to be less sensitive to the sedative effects of ethanol as measured by shorter recovery time from ethanol-induced sleep and did not develop rapid tolerance to ethanol-induced hypothermia, although plasma ethanol concentrations were not significantly different from those of controls. Our findings contrast with previous reports that showed that nonselective NOS inhibitors decrease alcohol consumption. However, because alcohol consumption was suppressed in wild-type as well as nNOS −/− mice by the NOS inhibitorNG-nitro-l-arginine methyl ester, we conclude that the effect of nonselective NOS inhibitors on alcohol drinking is not mediated by nNOS. Other NOS isoforms, most likely in the periphery or other splice variants of the NOS gene, might contribute to the effect of nonselective NOS inhibitors on alcohol drinking. In summary, the nNOS gene is critically involved in the regulation of neurobehavioral effects of alcohol.